Studi Kasus Gangguan Pola Napas Tidak Efektif Pada Pasien Efusi Pleura - Yunita Devi Anggarsari; Yuyun Setyorini; Akhmad Rifai (Interest : Jurnal Ilmu Kesehatan, 2018)
Background: Pleural effusion is a fluid above the normal in the pleural space. Widespread pleural effusions will cause shortness of breath that affects the fulfillment of oxygen demand, so that nursing interventions can be arranged one of them is to set the semifowler position and collaborate in the giving of O2. The purpose of this study was to obtain a picture and experience in providing nursing care significantly for patients with pleural effusion with respiratory disorders. Method: This study uses data analysis method that is comparing the results obtained from two patients with pleural effusions who experienced ineffective breathing disorder and then compared with case study journal or other sources. Result: Based on the results of interviews and observations concluded that with the same diagnosis and performed the same implementation there are differences in outcomes in the intervention group with the control group. Conclusion: Forward in this study is the need to pay attention to accuracy in conducting assessments to maximize data in determining the priority problems that occur in patients and interventions based ONEC (Observation, Nursing Treatment, Education, Collaboration).